Refugee Status Determination (RSD) in Albania - Dyduch, X (Refugee Studies Centre, University of Oxford, 2016)
A study of Refugee Status Determination decisions in Albania – a relatively new European country of destination – reveals some shortcomings, despite the country’s efforts to develop its procedures in line with international standards.